A Fibrosarcoma Case with Poor Prognosis in a Golden Retriever Breed Dog - Tanrısever, Murat; Karabulut, Burak; Cevik, Aydın (My University, 2020)
A ten-year-old male, Golden Retriever breed dog was brought to the surgical clinic with a sign ofswelling in the left pelvic region. The tumor suspected mass, located in the upper left of the pelvis,was totally excised. The mass of the tumor was approximately 1570 g and the size was 20x15x7cm. Histopathological examination of the tumor revealed fibrosarcoma. Chemotherapy was initiated1 week after the operation by using of vincristine sulphate 3 times per week. Recurrence startedagain in the same region about two weeks after the last chemotherapy. Approximately 4 weekslater, the second surgical operation was performed because the mass grow up again. Patient died8 hours after the last operation. In this case report, a case of fibrosarcoma with poor prognosis thatdid not respond to tumor surgery and chemotherapeutic treatment is presented.
Keywords: Genel ve Dahili Tıp; Onkoloji; Veterinerlik